#TITLE_ALTERNATIVE# - PRABU MENARA (NIM : 13607008); Pembimbing : Dr. Rianto Adhy Sasongko; Dr. Ing M. Agoes Moelyad, GANDI
This thesis discusses about modelling and simulation of dynamics system with flapping-wing micro aerial vehicle/ FMAV. Modeling needs to be done in order to know the characteristics of motion of the system. To obtain a mathematical model, performed by the method of approach to a rigid system of multiple objects (multiple rigid body) and Newton's Second Law, whereas for the aerodynamic forces approach used quasy-steady state approach. Basically, this method uses a system of equilibrium forces and moments acting on the system FMAV, such as gravity, aerodynamic forces and inertial forces. With this method, a mathematical model of the system FMAV has been obtained Furthermore, numerical simulations carried out also using MATLAB/SIMULINK. This simulation is reviewing several cases of aircraft, namely: the case of monitoring the flight (hovering) and several variations of equilibrium in the case of flying a vertical direction (against gravity) in the field of different wing. The simulation results showed that the orientation / attitude FMAV translational motion is affected by the condition / initial attitude of the wing movements FMAV. From the research results are expected to provide an overview of the theoretical attitude and dynamic nature of the system FMAV.